INFORMATICS IN UNIVERSAL EDUCATION SCHOOLS USE OF PEDAGOGICAL SOFTWARE AND PEDAGOGICAL TECHNOLOGIES IN TEACHING - Hakberdiyev Bahrom Bobonazarovich (American Journals Publishing, 2024)
Current problems of teaching informatics in modern schools were considered, and prospects for their solution were revealed. Ways of using pedagogical software in the process of computer science education are shown.
Keywords: Pedagogical software tools, pedagogical technologies, informatics, didactic goal, information culture, systematic nature of informatics, concept, Adobe Illustrator, vector, outline, raster.